Pioneers of the Facultad Ciencias de la Salud - Andrés Perafán-Simmonds; Carlos Cesar Perafán-Simmonds; Marcel Perafán-Simmonds (Revista de la Facultad de Ciencias de la Salud, 2017)
On December 2, 2017 marks the 100th anniversary of the birth of Julio César Perafán Fajardo, who was one of the pioneering doctors who made possible the foundation of the Facultad de Ciencias de la Salud of the Universidad del Cauca. He died on March 30, 2008, at 90 years of age. This editorial is a recognition of the work of a lifetime of Julio César Perafán, dedicated to the service of his city, its people and health sciences.